Polygenic Risk Scoring and Prediction of Mental Health Outcomes - Anderson, John S. (Curr Opin Psychol, 2018)
Psychiatric conditions are highly polygenic, meaning that genetic risk arises from many hundreds or thousands of genetic variants. Psychiatric genomics and psychological science are increasingly using polygenic risk scoring—the integration of all common genetic variant effects into a single risk metric—to model latent risk and to predict mental health outcomes. This review discusses the use of these scores in psychology and psychiatry to date, important methodological considerations, and potential of scoring methods for informing psychological science. Polygenic risk scores can easily be added to environmental and behavioral genetic models of latent risk, making them desirable metrics for use in psychological research.